2015
DOI: 10.1149/2.0231602jss
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Reaction Pathways for MOVPE Growth of Aluminum Nitride

Abstract: The chemical reaction pathways for metal-organic vapor phase epitaxial growth of aluminum nitride (AlN) were investigated using elementary reaction simulations and density functional theory calculations. We found that alkyl-aluminum amide (DMA-NH 2 ), which initiates parasitic chemical reactions such as oligomerization, is one of the major reactive species involved in AlN growth. The simulation results indicated that DMA-NH 2 is adsorbed on the surface, followed by the elimination of methane with no energy bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Quantum chemistry calculations based on the density functional theory (DFT) have been widely used to study the gas reaction mechanism of AlN MOVPE. Nakamura et al , studied the elimination reactions of TMX adducts (X = Al, Ga, and In) assisted by excess NH 3 , TMX, and the TMX adduct, respectively. They proved that the energy barrier for CH 4 elimination is reduced considerably in the excess NH 3 and the Al–N bond interaction is most strong in TMAl/NH 3 system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantum chemistry calculations based on the density functional theory (DFT) have been widely used to study the gas reaction mechanism of AlN MOVPE. Nakamura et al , studied the elimination reactions of TMX adducts (X = Al, Ga, and In) assisted by excess NH 3 , TMX, and the TMX adduct, respectively. They proved that the energy barrier for CH 4 elimination is reduced considerably in the excess NH 3 and the Al–N bond interaction is most strong in TMAl/NH 3 system.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been confirmed that the strong parasitic reactions between TMAl and NH 3 in TMAl/NH 3 /H 2 system are responsible for both nanoparticle generation and thin film growth, , the detailed reaction paths that lead to nanoparticles or stable gas precursors for AlN epitaxy are still unclear, and the existence of [AlN] 1–6 clusters is not justified. Besides this, previous researchers determined the reaction paths mainly by examining the changes of potential energy or Gibbs free energy along the reaction paths. However, the occurrence of a reaction along certain reaction path requires not only the Gibbs energy difference between the products and the reactants, Δ G , decreasing but also the Gibbs energy of activation, Δ G * , at the transition state being small among competing reactions . Thus, the previous sole potential energy or Gibbs energy criterion can not give correct predictions of reaction pathways in AlN MOVPE growth.…”
Section: Introductionmentioning
confidence: 99%
“…The rate and efficiency of the process are strongly dependent on reaction kinetics, fluid flow, heat transfer and mass transport in the reaction zone. An in-depth understanding of such reaction-transport phenomena requires computational fluid dynamics (CFD) models that are able to predict growth rate and its uniformity over complex geometries [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…2(b) , the pit issue is solved on the SPF sample attained by interrupting the NH 3 supply during the HT-AlN growth. Unlike the case in the CF sample, where the synthesis of AlN immediately takes place once the TMAl:NH 3 adduct or the monomethyl-Al (MMAl, decomposed from TMAl) reach the reactive surface 21 , 22 , the Al precursors decomposed during the NH 3 pulse interval are more likely to diffuse to the vacant atomic sites (created either by inherent in-plane strain or by H 2 partial etching) 23 , and thereby flatten the pitted surface. The other benefit of pulsed NH 3 flow can be explained using Fig.…”
Section: Resultsmentioning
confidence: 99%